Research progress of dissolving microneedles in the field of component administration of traditional Chinese medicine - Yang, Yuting; Zhang, Tingting; Niu, Baoshuo; Wang, Xiangyu; Liu, Liting; Zhu, Pengju; Meng, Fanda (Frontiers in Pharmacology, 2025)
In recent years, dissolving MNS technology, as an emerging transdermal drug delivery technology, has shown unique advantages and broad application prospects in the fields of transdermal drug delivery, transcutaneous immunity, beauty and skin care, food testing, and disease diagnosis. The active ingredients of traditional Chinese medicine have shown remarkable efficacy in treating various diseases. However, the mode of administration of traditional Chinese medicine (TCM) limits its potential for clinical application and promotion to a certain extent. The combination of dissolving MNS technology and transdermal administration of traditional Chinese medicine can not only simplify the application process of traditional Chinese medicine, but also promote the modernization process of traditional Chinese medicine and realize the “reduction,” “toxicity reduction,” and “efficiency increase” of traditional Chinese medicine. This article reviews the advances in the preparation and application research of dissolving MNS in traditional Chinese medicine. It provides a reference for further exploring the development and clinical application of efficient soluble MNS in traditional Chinese medicine.